Hubungan Religiusitas dan Pola Asuh Demokratis dengan Empati Siwa Kelas VIII MTs Negeri 14 Jombang - Adibah Adibah; Elsa Widjajanti Nurwijani (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
This study was aim to determine the relationship between religiosity and democratic parenting with the students’ empathy. The participants of this study were the eighth grade students of MTs Negeri 14 Jombang in the academic year 2019-2020. The data collection tools used in this study were the scale of religiosity, parenting scale and empathy scale that refers to Likert. The assumption test results showed that one of the linearity assumptions of the relationship is not fulfilled, then the data analysis technique which was originally used multiple and partial regression analysis was then replaced with nonparametric correlation analysis of ‘spearman's rho’level. The results of the spearman's rho level correlation between religiosity and empathy obtained rho = 0.327 and sig 0.039 (P <0.05). It means that there was a significant positive relationship between religiosity and empathy for students of class VIII MTsN 14 Jombang. The results of the spearman 's rho correlation between democratic parenting with empathy obtained rho = 0.367 and sig 0.020 (P <0.05) means that there was a significant positive relationship between democratic parenting with students’ empathy of class VIII MTsN 14 Jombang. Keyword: Religiosity; Democratic Parenting; Empathy